Bisphenol A Removal by Graphene Oxide Applied in Different Processes - EyÃ¼p Debik; Kubra Ulucan-Altuntas; Ahmed El Hadki (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Bisphenol A (BPA) is a commonly used plasticizer incorporated into the parent plastics during manufacturing. It is classified as an emerging contaminant that is continually detected in aquatic environments and is listed as an endocrine disrupting chemical confirmed to be associated with cardiovascular disease and reproductive disorder. The hazardous aspects of BPA require the development of innovative methods for its degradation. Among these techniques, adsorption and electrochemical degradation are considered to be particularly attractive due to their high efficiency, versatility and environmental friendliness, since they do not require any other chemicals. The use of graphene oxide (GO) was investigated as an adsorbent and as a particle electrode for the removal of BPA from aqueous solutions. The adsorptive behaviors of GO toward BPA were investigated in batch mode under darkness, visible light and UV light conditions. GO was used as particle electrode in a three-dimensional electro-oxidation (3D-EO) process established by an Ru/TiO2 anode and the effects of current density values ranging from 10 to 50 mA/cm2 were investigated. The obtained results revealed that the 3D electrochemical degradation process achieved a higher BPA removal efficiency than adsorption, showing that 3D-EO with a graphene oxide particle electrode may significantly improve BPA removal efficiency.